2014
DOI: 10.2196/med20.3213
|View full text |Cite
|
Sign up to set email alerts
|

Health Information on the Web and Consumers’ Perspectives on Health Professionals’ Responses to Information Exchange

Abstract: BackgroundHealth information technology, which is sometimes referred to as informaticization of medicine, is changing the extent to which patients become competent producers of their own health by enabling them access to health information anytime and anywhere.ObjectiveThis research provides preliminary information on users' perceptions of the extent to which use of the Internet for health information impacts medical encounters. We specifically explored the following questions: (1) To what extent perceptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
5
4
0
Order By: Relevance
“…Top 10 of the health-and/or nutrition-related websites cited by the participants of the NutriNet-Santé study, France information obtained on the Internet. Similar results have been reported by Seçkin et al (32) regarding educational level. Those subjects were also the ones more likely to consult non-institutional websites in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Top 10 of the health-and/or nutrition-related websites cited by the participants of the NutriNet-Santé study, France information obtained on the Internet. Similar results have been reported by Seçkin et al (32) regarding educational level. Those subjects were also the ones more likely to consult non-institutional websites in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, only 16 % of the participants discussed health/ nutrition information found on the web with a HCP. A similar proportion (17 %) was observed in Japan (22) , about 35 (7) and 50 % (9,32) were reported in US studies and 73 % in Saudi Arabia (31) . Renahy et al (18) showed that people who were more likely to search for health information on the Internet were those who would appreciate more attention from their physician and who were more inclined to think that physicians did not tell them everything about their health.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…There is growing evidence about how HRII is used in consultations [ 23 - 25 ]. For a range of reasons, however despite patients’ sourcing HRII, it may not feature in consultation discussions [ 26 ]. When HRII is discussed in medical consultations, it can have both positive and negative impacts [ 27 ] and does not always mark a shift toward patient-centeredness [ 28 ], particularly as patient and HCP perspectives on the role of HRII can differ [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…I speculate these forces may require clinicians to re-conceptualize themselves as collaborators in the health of increasingly empowered self-aware "patient-clients". [31][32][33] Additionally, movements towards open access, open educational resources, and open scholarship are all gaining momentum. [34][35] One intriguing example in health professional education is Osmosis-a method of learning used by more than 100,000 people around the globe.…”
Section: Future/evolving Trendsmentioning
confidence: 99%